GROUND WATER LEVEL AND VIBRATION EFFECT DUE TO BLASTING ACTIVITIES ON SLOPE STABILITY USING NUMERICAL METHOD IN PT. BUKIT ASAM, TBK. - Radita R. Sunusi, Arswinda
Slope stability is an important factor in the planning and operation of open pit mines. The design of stable and proper slopes will have a major impact on the economics and continuity of mine production. PT Bukit Asam, Tbk. is one of the coal mining companies in South Sumatra that uses the blasting method in dissolving its minerals, this aims to make production activities more effective and efficient but continuous blasting activities will certainly have a negative impact, one of which is ground vibration. Ground vibrations can occur because when detonation takes place, only part of the total energy produced by explosives is consumed to break the rock, the other part becomes residual energy which will propagate through the rock causing deformation in the rock but not breaking the rock because it is still within its elastic limit. In addition, groundwater can also provide problems in mine management. This is because the pore water pressure creates a lift force, which will reduce the strength of the rock mass that makes up the slope so that it can increase the risk of instability. This research was conducted with the aim of determining the stability of coal mine slopes in terms of static, pseudostatic and dynamic Safety Factor (FK) values as well as critical displacement values. The data used includes data on physical and mechanical properties in the form of cohesion and internal shear angles, data on blasting vibrations in the form of Peak Particle Acceleration with respect to time, as well as groundwater table measurements in the form of Hu 0, 0.6, 0.8, and 1. Analysis was carried out using the Newmark method using software 2 Dimensional (2D) slides. The results of the analysis with the Newmark method are permanent displacements for each reduction in rock mass strength. Critical displacement values and dynamic FK are obtained from the graph between the permanent displacement and the rock mass strength reduction factor. Based on the results of analysis on highwall and lowwall slopes, it can be seen that the smaller the value of rock mass strength and the more saturated the slope conditions, the greater the value of permanent displacement and critical displacement so that the value of the Safety Factor (FoS) is smaller while the value of Probability of Failure (PoF) will be higher. Stable criteria on static slopes are FoS ? 1.3 and PoF ? 5%, and on pseudostatic & dynamic slopes are FoS ? 1.1 and PoF ? 5%. FoS static value is greater than FoS dynamic and FoS dynamic value is greater than FoS pseudostatic.